Low Temperature Fabrication of Flower-Like Rutile Phased Tio2 Film towards Methyl Orange Degradation - K. A. Hamed, N.; K Ahmad, M.; H. Mazlan, M.; H.H. Hairom, N.; Nafarizal, N.; F. Soon, C.; Sanudin, R.; S. Aziz, H.; H. Mamat, M.; B. Suriani, A.; Shimomura, M.; Murakami, K. (International Journal of Engineering and Technology, 2019)
Pure rutile titanium dioxide (TiO2) thin film was fabricated at a low temperature of 150oC by using a simple, one step hydrothermal method. TiO2 thin film was developed on Fluorine doped tin oxide (FTO) by using titanium butoxide (TBOT) as a precursor, hydrochloric acid (HCl) and deionized (DI) water. The assembly of flower-like rutile phased TiO2 could be controlled by simply changing the amount of precursors. The prepared samples were characterized by using Field Emission Scanning Electron Microscopy, X-ray Diffraction and Energy-dispersive spectroscopy. Most importantly, this pure rutile TiO2 thin film showed a great significance compared to commercial TiO2 Degussa P25 on degradation of methyl orange under UV light. The degradation of rutile TiO2 thin film was up to 65.6 % while P25 thin film was only 8.07 %. From the experiments, it was found that the rutile phased TiO2 has the higher photocatalytic activity in lower MO concentration and favorable in acidic environment. The enhanced activity might be accredited to the efficient separation of electron-hole pairs and high surface area produced by flower-like rutile phased TiO2.Â